Georadar - high resolution geophysical electromagnetic device - Janez Stern; Boris Tomšič; Aleksander Brezigar; Glišo Rašković (Geologija, 1995)
Georadar is a high resolution geophysical electromagnetic device that was developed in the first part of the 1980's. In Slovenia it was first tested in 1991 on several objects of economicgeological, geotechnical and hydrogeologic nature.Here its usefulness in karst studied is presented. The first part of the paper deals with description of measurement procedure and methodological bases, and the second part with experience and results of case histories. Shown are radargrams from ornamental stone quarry Hotavlje, calcite mine Stahovica, Golobja jama karstcave near Divača and from highway construction site Razdrto-Čebulovica. All measurements were performed with the georadar instrument Pulse EKKO IV with a lOOMHz antenna according to the method of reflection profiling.